Patterns of urbanization and the question of multiculturalism and territorialization: an example in transitional society (Croatia) - Čaldarović, Ognjen (Array, 2006)
In the chapter major processes concerning social differentiation and segregation as well as territorialization of ethnicities are discussed and presented. The case of a transitional society such as Croatia is presented with an emphasis on current processes and potential future developments.